Rethinking schizophrenia in the context of normal neurodevelopment - Catts, Vibeke S.; Fung, Samantha J.; Long, Leonora E.; Joshi, Dispesh; Vercammen, Ans; Allen, Katherine M.; Fillman, Stu G.; Moore, Loretta; Rothmond, Debora; Sinclair, Duncan; Tiwari, Yash; Tsai, Shan-Yuan; et al. (Frontiers in Cellular Neuroscience, 2013)
The schizophrenia brain is differentiated from the normal brain by subtle changes, with significant overlap in measures between normal and disease states. For the past 25 years, schizophrenia has increasingly been considered a neurodevelopmental disorder. This frame of reference challenges biological researchers to consider how pathological changes identified in adult brain tissue can be accounted for by aberrant developmental processes occurring during fetal, childhood or adolescent periods. To place schizophrenia neuropathology in a neurodevelopmental context requires solid, scrutinized evidence of changes occurring during normal development of the human brain, particularly in the cortex; however, too often data on normative developmental change are selectively referenced. This paper focuses on the development of the prefrontal cortex and charts major molecular, cellular and behavioral events on a similar time line. We first consider the time at which human cognitive abilities such as selective attention, working memory and inhibitory control mature, emphasizing that attainment of full adult potential is a process requiring decades. We review the timing of neurogenesis, neuronal migration, white matter changes (myelination), and synapse development. We consider how molecular changes in neurotransmitter signaling pathways are altered throughout life and how they may be concomitant with cellular and cognitive changes. We end with a consideration of how the response to drugs of abuse changes with age. We conclude that the concepts around the timing of cortical neuronal migration, interneuron maturation and synaptic regression in humans may need revision and include greater emphasis on the protracted and dynamic changes occurring in adolescence. Updating our current understanding of post-natal neurodevelopment should aid researchers in interpreting grey matter changes and derailed neurodevelopmental processes that could underlie emergence of psychosis.